KAJIAN TEKNIS PEMELIHARAAN LARVA UDANG VANAME (Litopenaeus vannamei) DI HATCHERY PT. NUSA DHARMA LAUTAN, KECAMATAN KALIPURO KABUPATEN BANYUWANGI JAWA TIMUR - Atika Marisa Halim; Nasuki Nasuki; Prestisia Dewanti Purnama (Universitas Muhammadiyah Gresik, 2024)
The shrimp fry produced by hatcheries not according to standard. The problem is due to larval rearing techniques that do not comply with operational standards, Indonesian National Standards and Good Fish Hatchery Methods (CPIB). This causes the production of vaname shrimp larvae to be low, therefore it is necessary to increase the production of vaname shrimp larvae. Hatchery PT. Nusa Dharma Lautan is a vaname shrimp larva hatchery company located in Banyuwangi. Hatchery PT. Nusa Dharma Lautan has facilities that support technical activities for rearing larvae according to standards and has a CPIB certificate. So the aim of this research is to obtain technical data on rearing white shrimp larvae which includes tank preparation, media preparation, stocking of naupli, feed management, water quality management, larval growth monitoring, pest and disease control, harvest and post-harvest. This research was carried out during one shrimp seed rearing cycle at PT Nusa Dharma Lautan from March to June 2023. Research data was taken from three tanks (B10, B11 and B13). Naupli stocking density was 133-166 fish/liter. Naupli used from Hatchery PT. Situbondo Delta. Acclimatization is carried out using a flowtrough system for 45-60 minutes. The feed used is natural phytoplankton type Chaetoceros sp. and Artemia salina zooplankton as well as artificial feed in the form of liquid, powder and flakes (thin plates). The number of naupli stocked in B10 was 2400000 individuals with a density of 160 individuals/L, B11 was 2000000 individuals with a density of 133 individuals/L, B13 was 2500000 individuals with a density of 166 individuals/L. The survival results in each tank are 45% in the B10; 54.5.% in B11; 42.4% in B13. According to the data, the results of the survival rate are quite good because they exceed the SNI standard, at least 30%.